PENGEMBANGAN KEMAMPUAN BERBICARA (MAHARAH KALAM) BAHASA ARAB MELALUI PENDEKATAN BEHAVIORISME - Sitti Maryam (Institut Kariman Wirayudha Sumenep, 2024)
This article explains the ideal idea of learning Arabic for the basic level which includeslearning objectives and learning methods. The approach used in this article is a behaviorist approach with literature reviw sources. Because the more creative and innovative a teachers is in delivering Arabic language lessons. The more easily students will accept them, because this is the most important factor in achieving success in the Arabic language teaching and learning process. The results of this reseach show that behavirism is a current which believes that behavior must be an element of the single subject of psychology. Behaviorism is a revoltionary, powerful and influencial scholl that has relatively deep historical roots. Behaviorism was born a reaction to introspectionism and psychoanalysis, behaviorism wants to analyze only visible behavior that can be measurd and described. Key words: Arabic Language, Speaking ability, behaviorism approach